Results of the randomized comparative study of second-generation supraglottic airways in orbital osteosynthesis - Kostetskiy, I. V.; Shamrikov, A. A.; Bagin, V. A.; Kaliskin, A. A. (Vestnik anesteziologii i reanimatologii, 2020)
The objective: to assess and compare supraglottic airways of LMA-Supreme and i-gel during orbital osteosynthesis. Subjects and methods. 91 patients were included into the study. All of them underwent osteosynthesis of the orbit. The patients were randomly divided into two groups. LMA-Supreme group included 42 patients, while i-gel group included 49 patients. Results. The parameters of hemodynamics, gas exchange, and artificial pulmonary ventilation (APV) did not basically differ between the groups at different stages of the study. The oropharyngeal leak pressure differed between the groups at the end of surgery and made (Me – median, Q 1 and Q 3 – upper and lower quartiles): 28.0 (22.0; 30.0) and 21.0 (19.0; 27.0) mm WG the LMA-Supreme and i-gel groups, respectively; p = 0.021. A significant difference was observed in the insertion time of supraglottic airways (Me is the median, Q 1 and Q 3 are the upper and lower quartiles): 27.5 (19.3; 36.5) sec. for LMA-Supreme and 15.0 (13.8; 25.0) sec. – for i-gel; p = 0.001. When inserting the LMA-Supreme duct in 33 (78.6%) patients, jaw thrust maneuver, extension of the neck, etc. were required; while in the i-gel group, similar maneuvers were necessary in 18 (36.7%) patients; p < 0.001. The number of postoperative complications was minimal in both groups. Conclusion. Both supraglottic airways can be used with equal efficacy in osteosynthesis of the orbit. At the same time, the i-gel duct has an advantage over the LMA-Supreme in speed and simplicity of insertion. The LMA-Supreme had greater leak pressure at the end of surgery, which might be an advantage in patients requiring greater peak inspiratory pressure to provide effective APV.